Hubungan Pola Asuh Demokratis dan Konsep Diri Terhadap Perkembangan Kecerdasan Emosional - Septiani, Widyawati (Indonesian Journal of Guidance and Counseling: Theory and Application, 2017)
The purpose of this research find correlation democratic parenting and self-concept to the development of emotional intelligence of students , Population and sample of this research is class VIII SMP Negeri 1 Bojong. The sampling technique using techniques Prabobility Sampling (Simple random sampling). The sample in this study is 72 students. Analysis of data using multiple linear regression using the Statistical Packages for Social Science (SPSS). The results showed an association of democratic parenting and self-concept to the development of emotional intelligence class VIII SMP Negeri 1 Bojong. There is a democratic parenting style influences on the development of emotional intelligence to the effect of the partial value of 14.06%. There is the influence of self-concept on the development of emotional intelligence to the effect of the partial value of 23.32%. It showed no effect democratic parenting and self-concept to the development of emotional intelligence.